Are the Current Little League Pitching Guidelines Adequate? A Single-Season Prospective MRI Study. Issue 5 (19th May 2017) - Pytiak, Andrew V.; Stearns, Phillip; Bastrom, Tracey P.; Dwek, Jerry; Kruk, Peter; Roocroft, Joanna H.; Pennock, Andrew T.
Background: Little League throwing guidelines have recently been implemented in an attempt to lessen the growing number of elbow injuries occurring in youth baseball players. Hypothesis/Purpose: The purpose of this study was to examine pre- and postseason changes seen on magnetic resonance imaging (MRI) in youth baseball players' elbows in an attempt to identify risk factors for pain and MRI abnormalities, with a particular focus on the current Little League guidelines. We hypothesized that MRI abnormalities would be common in pitchers with high pitch counts and poor guideline compliance. Study Design: Cohort study; Level of evidence, 2. Methods: A prospective study of Little League players aged 10 to 13 years was performed. Players were recruited prior to the start of the season and underwent bilateral elbow MRI as well as a physical examination and completed a questionnaire addressing their playing history and arm pain. At the end of the season, a repeat MRI and physical examination were performed. MRIs were read by blinded radiologists. During the season, player statistics including innings played, pitch counts, and guideline compliance were recorded. Physical examination findings and player statistics were compared between subjects with and without MRI changes utilizing chi-square and analysis of variance techniques. Results: Twenty-six players were enrolled. Despite 100% compliance with pitching guidelines, 12 players (48%) had abnormal MRI findings, and 28% experienced pain during the season. There was a significant difference in distal humeral physeal width measured pre- to postseason (1.54 vs 2.31 mm, P < .001). There was a significant loss of shoulder internal rotation during the season, averaging 11°. While pitch counts, player position, and throwing curveballs/sliders were not significantly associated with changes seen on MRI, year-round play was associated with abnormalities ( P < .05). Much lower compliance (<50%) was observed with nonenforced guidelines, including avoidance of single-sport specialization, year-round play, and throwing curveballs/sliders. Conclusion: Arm pain and MRI abnormalities of the medial elbow are common in Little League baseball players who comply with the Little League throwing guidelines, especially those playing year-round.